Constitutional rights and obligations of citizens towards the environment under the conditions of sustainable development (Ius Novum, 2024)
The aim of this article is to determine the status of citizen’s rights to ‘a clean environment’ and their obligations towards the environment under sustainable development conditions, considering international and domestic regulations. It analyses three interlinked aspects: human rights to a clean environment, obligations of citizens and public authorities towards the environment, and environmental protection in accordance with the principle of sustainable development. Human rights to ‘a clean environment’ are enshrined in the Constitution, drawing on the Universal Declaration of Human Rights and the Rio de Janeiro ‘Environment and Development’ Declaration. These rights are implemented by public authorities through ensuring ecological safety and the useand protection of environmental resources, adhering to the sustainable development principle. In addition every citizen has obligations towards the environment, because he should take care of environmental resources and use them in accordance with the principles of environmental protection law. The analysis of legal doctrine and legislation highlights a clear relationship betweenthe necessity for public authorities to ensure constitutional rights to a ‘clean environment’ and their obligations towards the environment through the protection of environmental resources in line with the sustainable development principle. This entails balancing the human right to a ‘clean environment’ against the environmental right to the continuity and sustainability of resources(natural balance), while also ensuring economic growth. An example of these principles in action is Agenda 2030, currently being implemented in Poland and other EU Member States.